Serviço social e objeto de trabalho profissional: particularidades político-conceituais dos/as assistentes sociais na política de saúde de São Borja - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The aim of this study was to unveil how the social workers linked to health policy, in the municipality of São Borja show the expressions of the social question as a manifestation of the natural object of professional work. The research is qualitative and were interviewed four professionals social workers through the technique of structured interview. The method used was the Historical Materialism and Dialectical. In the course of study found a weak theory about the understanding of the social issue evident in the understanding of the existence of a new social issue, the difficulty of understanding it as an object of study, which contributed to the questioning of historical materialism and dialectics as the method best suited to the grounding of professional intervention, since it was identified in the course of data collection that the social workers learn to work in practice. It also became clear that the fragility theory takes the professionals interviewed to not have criteria for the definition of methodological strategies used to intervene, which results in the reproduction of the identity assigned. In turn, the political dimension taken in professional work is reduced to formal citizenship, since by fragility theoretical-methodological laws are confused with theory and the delivery is taken as a product of the intervention.
Keywords: Assistente social; Trabalho profissional; Questão social; Instrumentalidade; Dimensão política; Intervenção; CNPQ::CIENCIAS SOCIAIS APLICADAS